DAMPAK PARIWISATA TERHADAP TATA RUANG PERMUKIMAN - Wahyono, Sharfina Bella Pahleva; Sari, Suzanna Ratih (Jurnal Arsitektur ARCADE, 2020)
The tourism sector is currently one of the sectors that are relied upon to improve the economy of a region. Various types of tourism destinations emerge, one of which is a tourist destination that comes from settlements in the form of villages or tourist villages. This gives a variety of impacts including in terms of the social, cultural, economic, and spatial structure of the settlement. The writing of this article aims to get a theoretical foundation that can later support in solving the problem being studied and the writer can better understand the problem being studied. The method used in this paper is to review literature by gathering several journals that are relevant to the topic. The results of writing this article found that spatial changes that occur in settlements that add a new function as a place of tourism are a form of adaptation of people, people, and tourists (tour operators), with their environment in fulfilling these new functions in order to run well. The factors that influence changes in the layout of a settlement with the existence of tourism activities include type, location of tourism, and social-cultural community and tourists who visit.